Generational differences in online safety perceptions, knowledge, and practices. Issue 9 (1st September 2016) - Jiang, Mengtian; Tsai, Hsin-yi Sandy; Cotten, Shelia R.; Rifon, Nora J.; LaRose, Robert; Alhabash, Saleem
ABSTRACT: As Internet usage has proliferated in recent years so have online security threats. Internet users are increasingly susceptible to online security threats. Using a qualitative approach, this study conducted 18 focus groups to examine how three different generations perceive online safety, use coping strategies, and protect themselves online: Silent and GI generation (SGI) (born 1945 or earlier), older Baby Boomers (1946–1954), and Millennials (1977–1992). Results show that although each generation shares a variety of online safety concerns, SGIs and Boomers are more suspicious about online security, have less confidence in their abilities, are uncertain about the effectiveness of protection resources, perform fewer protection behaviors, and are more likely to rely on others' assistance compared to the Millennial group. Our findings indicate online safety training is needed for all three generations, but especially for older adults. Tailored approaches are suggested to reach different generations.